1999
DOI: 10.1542/peds.103.5.e60
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of an Acellular Pertussis Vaccine in Premature Infants

Abstract: Immunization with an acellular pertussis vaccine is safe for preterm infants. The immune response is significantly lower compared with a control group of term infants, but efficacy is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
6

Year Published

2005
2005
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 15 publications
(9 reference statements)
0
33
0
6
Order By: Relevance
“…The only possible exception is the increase in the rate of apnea (accompanied or not by bradicardia) and desaturation episodes, which is observed by most authors [12][13][14][15]. Observation of 473 premature infants of weight <1,500g (average weight -910g [375-1,495]), average GA of 27.6 (22.6-34.3) weeks and GA by the moment of vaccination of 37.4 (31.5-48.3) weeks showed that only 2.8% of children had generalized (fever) and local reactions; however, 10% of children had apneic episodes with/without bradicardia [16]. In a different observation of 411 premature infants (average GA -27 weeks, weight -<1,000g) after vaccination at the age of 2 months, apneic episodes required artificial pulmonary ventilation (APV) in 5.3% of children [17].…”
Section: Safety Of Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The only possible exception is the increase in the rate of apnea (accompanied or not by bradicardia) and desaturation episodes, which is observed by most authors [12][13][14][15]. Observation of 473 premature infants of weight <1,500g (average weight -910g [375-1,495]), average GA of 27.6 (22.6-34.3) weeks and GA by the moment of vaccination of 37.4 (31.5-48.3) weeks showed that only 2.8% of children had generalized (fever) and local reactions; however, 10% of children had apneic episodes with/without bradicardia [16]. In a different observation of 411 premature infants (average GA -27 weeks, weight -<1,000g) after vaccination at the age of 2 months, apneic episodes required artificial pulmonary ventilation (APV) in 5.3% of children [17].…”
Section: Safety Of Vaccinesmentioning
confidence: 99%
“…As a rule, these episodes develop within 48 hours, rarer -within 72 hours after vaccination; they are more often observed in children with short gestational period who have had similar episodes before vaccination. Risk factors also include apneic episodes 24 hours before immunization, severe postnatal condition, age of less than 70 days or weight less than 1,500g [11,16,18]. Absolutely not all registered apneic episodes are directly associated with vaccinal administration, as was shown by the controlled study of 197 children with GA ≤27 weeks and weight ≤1,000g: administration of a vaccine against diphtheria, tetanus and pertussis with acellular pertussis component (DTaP) on the 55 th -60 th day of life was not accompanied by a higher rate of complications in comparison with the non-vaccinated control group children.…”
Section: Safety Of Vaccinesmentioning
confidence: 99%
“…Otros estudios no han logrado confirmar esta asociación. Este fenómeno no se ha observado con el uso de vacunas antipertussis acelulares 12 .…”
Section: Reacciones Adversas a Vacunas En El Prematurounclassified
“…Este fenómeno no se ha observado al utilizar vacunas anti-pertussis acelulares 12 . Sin embargo, el costo de las vacunas acelulares y la naturaleza benigna de las convulsiones febriles hace discutible su uso sistemático en niños prematuros sin otros factores de riesgo de convulsiones.…”
Section: Reacciones Adversas a Vacunas En El Prematurounclassified
“…No entanto, existem relatos de apnéia até 72 horas após a administração da vacina tríplice bacteriana contra difteria, tétano e pertussis (DTP) (células inteiras) em RN < 31 semanas de idade gestacional, o que não foi observado após o uso da vacina acelular [18][19][20] . Crise convulsiva febril benigna também foi relatada mais freqüentemente em prematuros do que em nascidos a termo que receberam a vacina pneumocócica heptavalente concomitantemente à DPT (cé-lulas inteiras) e a vacina contra hemófilos do tipo b 6 .…”
unclassified